Factors related to genetic counseling, genetic testing, sharing information with relatives, and surveillance in von Hippel- Lindau syndrome: a retrospective study using genetic counseling records - Torishima, Masako; Kosugi, Shinji; Inaba, Akira; Yoshida, Akiko (Journal of Hereditary Tumors, 2024)
von Hippel-Lindau syndrome is a hereditary tumor for which early detection and early treatment are important. However, clinical diagnosis of the proband may not lead to information sharing and surveillance of relatives. The aim of this study was to explore factors leading from probands’ genetic counseling visits to surveillance visits for relatives. We reviewed 75 genetic counseling records from a 10-year period at Kyoto University Hospital and conducted thematic analysis. The subjects of this study were 41 patients from 26 families. The purpose of the genetic counseling visit was “to undergo genetic testing” (33 clients, 80.5%). The reason for the proband’s visit was “learning that the genetic test results of the proband were necessary for the genetic testing of relatives” (six out of 19 probands, 31.6%). The reason for relatives’ visits was “recommended by parents” (11 out of 22 cases, 50.0%). This study observed various facilitating factors and barriers related to GC visits, undergoing GT, sharing information with relatives, and undergoing surveillance. Our findings suggest that it is important to involve other family members to share the burden, explain the significance of genetic testing and surveillance to the proband, and facilitate genetic counseling appointments.